2000
DOI: 10.2337/diacare.23.11.1630
|View full text |Cite
|
Sign up to set email alerts
|

Associations between alcohol consumption and insulin sensitivity and cardiovascular disease risk factors: the Insulin Resistance and Atherosclerosis Study.

Abstract: Associations Between Alcohol Consumption and Insulin Sensitivity and Cardiovascular Disease Risk FactorsThe Insulin Resistance and Atherosclerosis StudyOBJECTIVE -Light-to-moderate alcohol consumption has been associated with reduced cardiovascular disease (CVD) mortality, which may be explained by increased insulin sensitivity (S I ) and an improved lipoprotein and blood pressure profile. Prior research has shown improved S I with light-to-moderate alcohol intake even though somewhat imprecise measures of S I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
90
1
5

Year Published

2001
2001
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 150 publications
(111 citation statements)
references
References 44 publications
15
90
1
5
Order By: Relevance
“…This finding strongly supports the idea proposed in some human studies of an inverse Ushaped relationship between alcohol intake and insulin sensitivity (12,14,15). However, it is reasonable to assume that at higher alcohol concentrations the inverse U-shaped relationship changes to an inverse J-shaped relationship since other human and animal studies have demonstrated that ethanol consumption can impair insulin-mediated glucose uptake and cause insulin resistance (17)(18)(19).…”
Section: A B C Dsupporting
confidence: 75%
See 1 more Smart Citation
“…This finding strongly supports the idea proposed in some human studies of an inverse Ushaped relationship between alcohol intake and insulin sensitivity (12,14,15). However, it is reasonable to assume that at higher alcohol concentrations the inverse U-shaped relationship changes to an inverse J-shaped relationship since other human and animal studies have demonstrated that ethanol consumption can impair insulin-mediated glucose uptake and cause insulin resistance (17)(18)(19).…”
Section: A B C Dsupporting
confidence: 75%
“…Since these controversial observations have not been unraveled to date and the human studies leave some gaps in the complete understanding of the association of light-to-moderate alcohol consumption and insulin sensitivity (15), it was the aim of this study to establish a reliable animal model that will allow more detailed investigations. Male Wistar rats received drinking water without (control) or with different ethanol concentrations (0.5, 1.5, 3, 4.5 and 7%, v/v) for 4 weeks ad libitum.…”
mentioning
confidence: 99%
“…Epidemiological studies suggest that chronic light or heavy ethanol consumption leads to insulin resistance, whereas moderate ethanol consumption results in increased insulin sensitivity [37][38][39][40][41] . In the present study, we found that long-term high-dose ethanol consumption led to insulin resistance in rats, which was consistent with previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…There are biologically plausible explanations for our findings. Among people without diabetes, moderate alcohol consumption may enhance insulin sensitivity [43][44][45][46][47][48][49][50][51] and has been shown to decrease A1C. [52][53][54][55][56] It is plausible that regular, moderate alcohol consumption by people with diabetes similarly enhances insulin sensitivity and improves glycemic control.…”
Section: Discussionmentioning
confidence: 99%